2020
DOI: 10.1080/21655979.2020.1765500
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological and prognostic value of CD44 expression in bladder cancer: a study based on meta-analysis and TCGA data

Abstract: CD44 is reported to be involved in tumor invasion and metastasis. However, the role of cancer stem cell marker CD44 in bladder cancer still remains controversial. Hence, the correlations between CD44 expression and the clinicopathological features and the prognosis of bladder cancer were investigated. Publications using immunohistochemical methods were identified. The Cancer Genome Atlas (TCGA) data were also analyzed. The odds ratios (ORs) or hazard ratios (HRs) with their 95% confidence intervals (95% CIs) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…As shown in Supplementary Fig 3 , ITPR3 and CSC markers such as CD44, SOX2 and OCT4 were enriched in BCa stem cells, which indicated that ITPR3 might play a vital role in maintaining the cancer stemness phenotype. We demonstrated that ITPR3 depletion suppressed cancer cell proliferation, migration, invasion and stemness by inhibiting the expression of CD44, which is the main cancer stem cell marker in bladder cancer 40 .…”
Section: Discussionmentioning
confidence: 92%
“…As shown in Supplementary Fig 3 , ITPR3 and CSC markers such as CD44, SOX2 and OCT4 were enriched in BCa stem cells, which indicated that ITPR3 might play a vital role in maintaining the cancer stemness phenotype. We demonstrated that ITPR3 depletion suppressed cancer cell proliferation, migration, invasion and stemness by inhibiting the expression of CD44, which is the main cancer stem cell marker in bladder cancer 40 .…”
Section: Discussionmentioning
confidence: 92%
“…4, ITPR3 and CSC markers such as CD44, SOX2 and OCT4 were enriched in BCa stem cells, which indicated that ITPR3 might play a vital role in maintaining the cancer stemness phenotype. We demonstrated that ITPR3 depletion suppressed cancer cell proliferation, migration, invasion and stemness by inhibiting the expression of CD44, which is the main cancer stem cell marker in bladder cancer 39 . NF-κB (nuclear factor (NF)-kappa B) serves as a transcription factor and has been reported to activate various genes, including in ammatory cytokines and oncogenes, which suppress the apoptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…3 , ITPR3 and CSC markers such as CD44, SOX2 and OCT4 were enriched in BCa stem cells, which indicated that ITPR3 might play a vital role in maintaining the cancer stemness phenotype. We demonstrated that ITPR3 depletion suppressed cancer cell proliferation, migration, invasion and stemness by inhibiting the expression of CD44, which is the main cancer stem cell marker in bladder cancer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%